Cover Feature: The Earlier the Better: Structural Analysis and Separation of Lanthanides with Pyrroloquinoline Quinone (Chem. Eur. J. 44/2020). Issue 44 (13th July 2020) - Lumpe, Henning; Menke, Annika; Haisch, Christoph; Mayer, Peter; Kabelitz, Anke; Yusenko, Kirill V.; Guilherme Buzanich, Ana; Block, Theresa; Pöttgen, Rainer; Emmerling, Franziska; Daumann, Lena J.
Abstract : Lanthanides can be separated by precipitation using the naturally occurring redox cofactor pyrroloquinoline quinone (PQQ). Complexes with early lanthanides are preferentially formed and rapidly precipitate out of aqueous solutions in the reported separation method. In addition, the first molecular structure of a PQQ complex with a biologically relevant metal ion outside a protein environment is reported and shows a Eu2 PQQ2 dimer. More information can be found in the Full Paper by L. J. Daumann et al. on page 10133 .